(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the necessity, methodological foundations, and practical directions for developing the creative competence of future educators in the modern educational process. During a period when experiential learning principles are becoming widespread in education globally, preparing educators who are creative thinkers, capable of solving problems independently, and approaching professional activities innovatively is one of the pressing issues. The article illuminates the scientific foundations of the concept of creativity in pedagogical activity, drawing on the views of both foreign and local scholars. It examines the technologies and models used in the development of creative competence. Additionally, the scientific and theoretical foundations for fostering creativity in the pedagogical process based on a competency-based approach are presented.